Titanium dioxide film based photocatalytic application for degradation of dyes - Abd Hamed, Noor Kamalia; Ahmad, Mohd. Khairul; Mazlan, Muhammad Hazli; Hayati Hairom, Nur Hanis (Penerbit Uthm, 2019)
Titanium dioxide (TiO2) is a potential material as a photocatalyst for environment remediation including photocatalytic degradation of organics pollutants in waste water treatment, dye sensitized solar cell (DSSC), self-cleaning panels and sensors. Although, a numerous number of methods have been employed to fabricate TiO2 film, the cost of the film is highly depending on sophisticated machine and hence, made the fabrication costly. Simple and cost-effective films have been introduced in dye degradation via the photocatalytic process. Dyes are organic pollutants or the by-product of food and printing industries. Due to high demands from society for food and printing, the wastes produced are relatively high and harmful to the environment. Hence, TiO2 film fabricated using hydrothermal method was proposed for the degradation of dyes. In this chapter, the photocatalytic property of TiO2 thin film for degradation of dyes and the advantage of TiO2 film will be discussed.